Cybersecurity risk analysis of multifunctional UAV fleet systems: a conceptual model and IMECA-based technique - Zemlianko, Heorhii; Kharchenko, Vyacheslav (Radìoelektronnì ì komp'ûternì sistemi (Online), 2023)
The subject of this study is to ensure the cybersecurity of systems of multifunctional UAV fleets (SMF UAV). The purpose of this study is to identify and analyze the risks associated with the cybersecurity of multi-functional UAV fleets, develop models of threats, vulnerabilities, and attacks, and conduct IMECA analysis of cyber-attacks. Tasks: 1) analyze threats that may affect the security of multifunctional UAV fleets; 2) identify system vulnerabilities and their possible consequences in case of exploitation; 3) develop models of the system infrastructure and threats, vulnerabilities, and attacks, considering the specifics of the functionality and communication between system elements; 4) perform a risk-based analysis, identifying and classifying potential threats and their impact. The following results were obtained. The following results were obtained. 1. Cybersecurity threats to multifunctional UAV fleets are described and classified. 2. Identified and analyzed system vulnerabilities and their potential consequences. 3. Developed models of threats, vulnerabilities, and cyberattacks, considering the specifics of the UAV fleet. 4. Conducted a risk-based analysis, determined the level of threat, and developed recommendations for improving the cybersecurity of the UAV fleet based on the results of the IMECA analysis. Conclusions. The research emphasizes the importance of the developed model and tool for the detection and analysis of cyber threats to the SMF UAV. This allows increasing the cybersecurity and reliability of the system and ensuring timely response to cyber threats. Areas for further research: development of a model and method to consider the specifics of cyber threats and the technological characteristics of the SMF infrastructure; development and implementation of proactive protection tools in the context of combined cyber-attacks; and expansion of the scope of these tools in various industries, including smart cities.